More Than Money: Correlation Among Worker Demographics, Motivations, and Participation in Online Labor Market - Chen, Wei-Chu; Suri, Siddharth; Gray, Mary L. (The 13th International AAAI Conference on Web and Social Media (ICWSM), 2019)
Most prior research about online labor markets examines the dynamics of a single work platform and either worker demographics or motivations associated with that site. How demographics and motives correlate with each other, and with engagement across multiple platforms, remains under-studied. To bridge this gap, we analyze survey responses from 1700 people working across four different online labor platforms to understand: What motivates people to participate in online labor markets and how do individual motives correspond to larger demographic patterns and structural dynamics that more broadly shape traditional employment opportunities? Our results show that age, gender, education, and number of income sources help explain who does on-demand work, when they do it, and why. Even more striking, these broader social dimensions of work correlate with when and why individuals work across multiple on-demand platform companies. Together, these factors structure on-demand labor markets more than individual choice or the presumed “flexibility” of on-demand work alone.